2014
DOI: 10.1016/j.imr.2014.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic antioxidant action of Phikud Navakot ameliorates hydrogen peroxide-induced stress in human endothelial cells

Abstract: BackgroundPhikud Navakot (PN), a combination of nine herbs, has been used traditionally in Thai medicinal formulas to relieve circulatory disorder. The present study aimed to compare the synergistic antioxidant efficacy and toxicity of the hydroethanolic and water extracts of PN at cellular level.MethodsPN and its nine herbs were extracted with either 50% ethanol or water. All extracts were tested for in vitro antioxidant potential using standard antioxidant assays. Evaluation of cytotoxicity, genotoxicity, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…Like other studies, herbal plants and plant-derived antioxidant, such as flavonoids, orientin, and luteolin, have been used to alleviate oxidative stress on erythrocyte [16, 22, 23]. PN also has antioxidative effect to protect hemolysis corresponded to our previous studies that claim an antioxidative property of PN on endothelial stress and oxidative stress induced by apoptosis [13]. Inhibitory effect of PN on cellular apoptosis is relevant to the integrity of red blood cell.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…Like other studies, herbal plants and plant-derived antioxidant, such as flavonoids, orientin, and luteolin, have been used to alleviate oxidative stress on erythrocyte [16, 22, 23]. PN also has antioxidative effect to protect hemolysis corresponded to our previous studies that claim an antioxidative property of PN on endothelial stress and oxidative stress induced by apoptosis [13]. Inhibitory effect of PN on cellular apoptosis is relevant to the integrity of red blood cell.…”
Section: Resultsmentioning
confidence: 77%
“…Our previous studies demonstrated that PN has several advantage effects to cardiovascular system, for instance, vasorelaxation [11], blood flow enhancement [12], and induction of glucose catabolism [12]. Recently, we found that PN ameliorates endothelial stress, attenuates oxidative stress induced by apoptosis, and prevents platelet aggregations [13]. However, high dose oral administration and prolong usage are contraindication in association with mesangiolysis [14].…”
Section: Introductionmentioning
confidence: 99%
“…Nine additional articles were identified through manual searches of the references, bibliographies and consultations with experts. This yielded 24 articles which met the inclusion criteria including 2 in vitro cell lines or bacteria (Sripanidkulchai et al, 2007;Tepsuwan et al, 2011), 3 in vitro cell-free (Channarong et al, 2012;Nalinratana et al, 2014;Tuekaew et al, 2014), 5 in vitro animal tissue studies (Chantharangsikul et al, 2009;Nonthasawadsri et al, 2015;Nusuetrong et al, 2012;Pataloong and Sawasdimongkol, 1995;Suvitayavat et al, 2005b), 13 in vivo animal studies (Chavalittumrong et al, 2009;Intayoong, 2006;Jariyapongskul et al, 2006;Kengkoom and Ampawong, 2015;Kengkoom et al, 2012;Matangkasombat, 1974;Nernpermpisooth et al, 2015;Sirisangtragul and Sripanidkulchai, 2013;Sirisangtrakul and Sripanidkulchai, 2011;Suvitayavat et al, 2004;Suvitayavat et al, 2005a;Thongpraditchote et al, 1999) and 1 human study (Suvitayavat et al, 2005) (Fig 1).…”
Section: Search Resultsmentioning
confidence: 99%
“…While several authors illustrated HPLC chromatograms of their extract, only 3 studies (Nalinratana et al, 2014;Sirisangtragul and Sripanidkulchai, 2013;Sirisangtrakul and Sripanidkulchai, 2011) compared different extraction methods and concluded that methylene chloride yielded most peaks with MeCl 2 extraction, MeOH showed some similarities, while aqueous extraction showed markedly fewer peaks (Nalinratana et al, 2014). Only one study identified peaks (Nalinratana et al, 2014). Three other studies (Suvitayavat et al, 2004;Suvitayavat et al, 2005a;Suvitayavat et al, 2005b) provided HPLC chromatographs but the nature of individual peaks were not identified and the rationale for showing them unclear.…”
Section: Quality Assessmentmentioning
confidence: 99%
See 1 more Smart Citation